Low-grade myofibroblastic sarcoma of the head and neck region: a report of two cases of this extremely rare type of sarcoma and review of literature - Jonnalagadda, Sashikanth; Khan, M. Abdul Amjad; Buddhavarapu, Kiranmayee; Betham, Prateek Raj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Sarcoma of the head and neck are rare and account of less than 1% of all tumors in head and neck region. Low grade myofibroblastic sarcomas (LGMFS) are even rare with only handful of cases ever reported in head and neck. We review 2 cases with LGMFS of maxilla and mandible. Retrospectively reviewed 2 patients who carried histological diagnosis of LGFMS. Previous clinic, operative and referral notes were reviewed along with histopathology slides and radiological studies. A 37-year-old female presented with recurrent right maxillary sinusitis and on CT scan was found to have an expanding mass in right maxillary sinusitis. Biopsy revealed it to be a LGMFS. She underwent total maxillectomy with orbital floor reconstruction, post operative radiation and is disease free for 18 months. A 49-year-old female presented with radiolucent mass on routine radiological examination. Initial enucleation and biopsy revealed it to be a LGMFS and was later treated with segmental mandibulectomy and fibular free graft reconstruction and post-operative radiotherapy. LGMFS of the bone is extremely rare tumor with only 8 cases being reported earlier from the skeletal system in entire body. Most common mode of presentation is asymptomatic mass found incidentally. These tumors are malignant with a rare propensity to metastasize distally. Hence prompt and accurate histological diagnosis followed by wide surgical excision with adjuvant therapy form important tenets of management.